Solubilización de fuentes de fósforo asociadas a un compuesto orgánico enriquecido con biofertilizantes - Rosatto-Moda, Leandro [UNESP]; de Mello-Prado, Renato [UNESP]; Castellanos-Gonzáles, Leónides; Reyes-Hernández, Alfredo; Caione, Gustavo [UNESP]; Silva-Campos, C.Naudi [UNESP] (My University, 2014)
The enrichment of an organic compound with biofertilizers of microorganisms (solubilizing phosphorus bacteria, BSF) can improve the properties of phosphate fertilizers applied to soils to increase nutrient availability. The experimental design was randomized complete blocks with a factorial 4×2 +1 arrangement of treatments: 1) four sources of phosphorus: phosphate rock, natural phosphate, triple superphosphate (TSP) and Cuban phosphate rock; 2) two sources of bio-fertilizer prepared from filter cake (cane waste) enriched with microorganisms and no enrichment; 3) and an absolute control (no filter cake or fertilizer); repeated three times. Data was analyzed with ANOVA and treatment means were compared using Tukey (p≤0.05). Assessments of available P (Bray-2 and Oniani methodology) and the quantification of total and solubilizing bacteria and fungi in the soil were performed 30, 60 and 90 d after starting the experiment. After 60 d, the population of BSF was lower in the control (p≤0.05) and the content of P (Bray-2) was higher for SFT (p≤0.01). The application of the bio-fertilizer increased the P content compared to the control. At 90 d P (Bray-2) increased with the SFT treatment, which also increased (p≤0.01) P in the soil at 60 and 90 d regardless of the presence of microorganism-enriched bio-fertilizer. The use of filter cake enriched with microorganisms associated with different sources of P, and applied to the soil with a high content of P, did not change the soil populations of total and solubilizing bacteria and fungi in the short term. TSP promoted the highest levels of P in the soil, irrespective of the presence of the organic compound enriched with P solubilizing microorganisms.
Solubilization of phosphorus sources associated with an organic compound enriched with biofertilizer
Keywords: Available P; Microorganisms; Natural phosphate; Triple superphosphate